Analyze Return on Equity and Weighted Average Cost of Capital Linkages to Firm Value - Deuis kartinah; Dicky Jhoansyah; Faizal Mulia Z (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
The company's stock price which always experiences a decline is the background of this research. This study aims to determine the effect of return on equity (ROE) and Weighted Average Cost of Capital (WACC) on firm value in the textile and garment sector which is listed on the Indonesia Stock Exchange. This study using secondary data from is Financial statements of textile and garment companies from 2013 to 2018 obtained through the website Indonesia Stock Exchange. The analytical method used is multiple linear regression and data analysis using IBM Statistics 26. Based on the result of the analysis it can be concluded that return on equity and weighted average cost of capital has a significant effect on firm value with R2 equal to 0,329, which means the contribution of the independent variable to firm value by Price book value (PBV) in textile and garment companies is equal to 32,9 % and the remainder equal to 68,1 % can be explained by other variables outside this study, and based on the value of F with the values 6.606 shows that the simultaneous correlations of independent variables namely ROE and WACC with the dependant variable firm value.